Modelagem e projeto de nova topologia CC-CC híbrida e bidirecional composta por um conversor push-pull e uma célula a capacitor chaveado - Sá, Marcos Victor Dantas de (2020)
DC-DC power conversion has gained greater importance in recent years, due to the increased use of distributed generation, electric vehicles, energy storage and uninterrupted power supplies. In these applications it is common to have situations in which the positioning of the load and the power supply alternate, which highlights the study of bidirectional converters. This work proposes a new bidirectional hybrid DC-DC converter topology that is composed of a push-pull converter connected to a ladder switched-capacitor cell. The advantages of this topology are bidirectionality, soft switching, high gain, natural voltage clamping, voltage switch reduction and high frequency isolation. In addition, it will be presented the analysis of the converter stages of operation, deduction of mathematical equations of static gain and design, dynamic modeling of the converter to obtain the control loop and numerical example, as well simulation results to prove the converter correct operation.